Quality of Life and Renal Functional Status In Patients With Cutaneous Ureterostomy and Ileal Conduit Urinary Diversion after Radical Cystectomy (Bangladesh Journal of Urology, 2020)
Introduction: Radical cystoprostetectomy in male patients and anterior pelvic exenteration in female patients coupled with en-block pelvic lymphadenectomy and urinary reconstruction or diversion remains the gold standard surgical approach to muscle invasive bladder cancer in the absence of metastatic disease. In Bangladesh, commonly performed urinary diversions are Cutaneous ureterostomy and Ileal conduit. Types of urinary diversion have a great impact on different aspects of quality of life (QoL) as well as post -operative renal function.Aims and Objectives: This study was designed to compare the Quality of Life and Renal Function in between Cutaneous ureterostomy and Ileal conduit urinary diversion after radical cystectomy.Methodology: This was a hospital based Quasi Experimental study in which patients were selected by purposive sampling and, conducted from July, 2017 to September, 2018 in the department of Urology Bangabandhu Sheikh Mujib Medical University. This study was performed among the patients with muscle invasive bladder cancer treated by radical cystectomy with cutaneous ureterostomy or Ileal conduit fulfilling the exclusion and inclusion criteria. Total 34 patients were taken for the study, among them 17 for cutaneous ureterostomy and, 17 for Ileal Conduit Group. Quality of Life was assessed through EORTC-QLQ-C30 questionnaire both pre and post operatively (3 months after operation). Renal function was assessed before and 1st POD, 7thPOD, one month and three months after operation by measuring eGFR.Result: Mean age of the patients was 59.00 ± 8.60 years and 53.35 ± 8.43years in group- A (Cutaneous ureterostomy) and group-B (Ileal conduit) respectively. Three months after operation, overall QoL in all scales were improved in both group but, more improvements were noted in group-B than group-A which were statistically significant (p